2004
DOI: 10.1261/rna.7190104
|View full text |Cite
|
Sign up to set email alerts
|

Interference probing of rRNA with snoRNPs: A novel approach for functional mapping of RNA in vivo

Abstract: Synthesis of eukaryotic ribosomal RNAs (rRNAs) includes methylation of scores of nucleotides at the 2-O-ribose position (Nm) by small nucleolar RNP complexes (snoRNPs). Sequence specificity is provided by the snoRNA component through base-pairing of a guide sequence with rRNA. Here, we report that methylation snoRNPs can be targeted to many new sites in yeast rRNA, by providing the snoRNA with a novel guide sequence, and that in some cases growth and translation activity are strongly impaired. Novel snoRNAs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 48 publications
2
40
0
2
Order By: Relevance
“…Consistent with this hypothesis, our previous data showed that the deleterious snoRNAs usually under-accumulate. 5,6 Taken together, the results demonstrate that mis-targeting methylation can impair both ribosome synthesis and function. The growth defects are most likely due to methylation rather than an antisense interference effect caused by the new snoRNP, as evidenced by these Figure 4.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I Smentioning
confidence: 68%
See 3 more Smart Citations
“…Consistent with this hypothesis, our previous data showed that the deleterious snoRNAs usually under-accumulate. 5,6 Taken together, the results demonstrate that mis-targeting methylation can impair both ribosome synthesis and function. The growth defects are most likely due to methylation rather than an antisense interference effect caused by the new snoRNP, as evidenced by these Figure 4.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I Smentioning
confidence: 68%
“…We have also observed similarly sharp positional effects for two other sensitive sites examined in both 18S and 25S rRNAs. 6,7 Our discovery that novel methylations can trigger severe rRNA degradation shows that modification or snoRNP effects are monitored during ribosome synthesis by some surveillance system(s), either directly or indirectly. Consistent with this view, it has been shown in Schizosaccharomyces pombe that substitution mutations at several positions in the PTC region that are normally methylated or pseudouridylated also caused degradation of rRNA.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I Smentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, when expressed in the cell, artificial snoRNAs can also efficiently guide rRNA modifications at target sites (Cavaille et al 1996;Ni et al 1997;Liu et al 2001Liu et al , 2008Liu and Fournier 2004).…”
Section: Introductionmentioning
confidence: 99%